DPPH free radical scavenging activity and total phenolic content of Libas (Spondias pinnata (L.f.) Kurz) leaves. - Pagdato, Shannen Jhen C (2013.)
Spondias pinnata (L.f.) Kurz commonly known as Libas is one of the edible, lesser known and indigenous tree species in the Philippines often used as flavoring. The lack of information on the antioxidant potential of the leaves of Spondias pinnata (L.f.) Kurz coupled with the need to discover a cheap, natural source of alternative dietary antioxidant to replace the synthetic and toxic ones have led to the search of new antioxidant source. The study was conducted to determine the antioxidant activity of Spondias pinnata (L.f.) Kurz leaves by evaluating its DPPH radical scavenging activity and total phenolic content using crude methanol, n-hexane and dichloromethane extracts. The methanol extract had the highest DPPH scavenging activity at 250 mg/L concentration, followed by hexane and then by DCM extracts. One - Way Analysis of the Variance (ANOVA) revealed that the percent free radical scavenging activity of the methanol plant extract is significantly different with that of the positive control, BHT. The methanol extract of S. pinnata also had the highest percent relative activity among the three extracts at 250 mg/L concentration, which was 2.7 fold higher than the percentrelative activity of the positive reference standard. The antioxidant activity of the two other extracts, n-Hexane and DCM, do not have significant difference compared to BHT. These results indicate that the leaf extracts of Spondias pinnata (L.f.) Kurz is a good free radical scavenger and can therefore be a possible alternative, readily available antioxidant.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Libas leaves